Influence of the application of enemas with oily extract of curcumin (Curcuma longa) on the tissue content of neutral and acidic mucins in the colonic mucosa without fecal stream - Martinez,Carlos Augusto Real (2017)
ABSTRACT Purpose: To verify if the application of enemas containing oily extracts of curcumin preserves the tissue content of mucins in the glands of the colonic mucosa without fecal stream. Method: Thirty-six Wistar rats were submitted to diversion of the fecal stream by proximal colostomy and distal mucous fistula. The animals were subdivided into three groups, and accordingly received enemas with saline and oily extract of curcumin at concentrations of 50 mg/kg/day or 200 mg/kg/day. After two or four weeks of intervention, the irrigated colic segments were removed. Neutral and acidic mucins were identified by Periodic-acid Schiff and Alcian-Blue techniques, respectively. The content of both mucin subtypes was measured by computerized morphometry. Mann-Whitney test was used to analyze the results, adopting a significance level of 5% (p ≤ 0.05). Results: There was an increase in the tissue content of neutral mucins in animals treated with curcumin at a concentration of 50 mg/kg/day for four weeks, whereas in the group treated with 200 mg/kg/day there was an increase independent of the time of intervention. The content of acidic mucins increased in animals treated with 200 mg/kg/day regardless of the intervention time, whereas in those treated with 50 mg/kg/day an increase was observed only after four weeks. Conclusion: Enemas with curcumin preserve the content of neutral and acidic mucins in the colonic epithelium without fecal stream.